ACCELERATION OF CURRICULUM 2013 IMPLEMENTATION MODEL FOR HIGH SCHOOL FRENCH LANGUAGE TEACHER OF YOGYAKARTA THROUGH LESSON STUDY - Roswita L.Tobing; Dwiyanto Djoko Pranowo; Rohali Rohali (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
This article is the result of research that aims to develop a model of the acceleration of the implementation of the curriculum 2013 at the high school French teacher of Yogyakarta. Curriculum 2013 is characterized by the emphasis on competence development attitude (character), skills, and cognition in a balanced way than the previous curriculum. Through Lesson Study attempted acceleration of understanding and competence of teachers in implementing the curriculum 2013 which has been announced by the government to be implemented in schools starting in June 2013. With workshops and modeling, high school French teachers dissect and understand the curriculum and develop lesson plans and teaching materials development which is ready to be applied from class X to class XII. The study was conducted by the Research and Development that begins with preresearch, followed by model development, testing product, and the final product is a complete learning tool with a final evaluation and learning for all semesters in high school level. The research was done in collaboration with teachers, members of French teacher assosiation (MGMP) in Yogyakarta. The results showed that through Lesson Study, the teachers' competence to implement the curriculum in the classroom is increasing. It is evident from the learning products produced jointly by teachers in the form of Lesson Plan (RPP) and the material and complete the evaluation. In addition, the emphasis on attitude competencies (development of character education can be customized by the teacher in teaching materials based on the syllabus of the curriculum 2013). Keywords: curriculum 2013, attitude, character, skills, cognition, Lesson Study, research and development